A Comprehensive Approach on Postnatal Care Services in Rural India Modeled on World Health Orgazation (WHO) Recommendations - Aarthy; BOORNEMA A RA; ANANTHARAMAN V V (Universitas Airlangga, 2026)
Every pregnancy and childbirth is unique. Although all three phases of maternal care are equally significant, the postnatal phase is the least well supported, with greater emphasis and resources placed on the antenatal and intrapartum periods. The primary purpose of optimal postnatal care is to prevent long-term complications and reduce maternal and neonatal mortality. This study assesses all twelve WHO-recommended postnatal care components under a single framework and examines the sociodemographic factors influencing their utilization. A community-based cross-sectional study was conducted among postnatal mothers in a rural block of Tamil Nadu, India. A total of 220 postnatal mothers were selected through multistage random sampling and interviewed using a pretested semi-structured questionnaire. Data were analysed using SPSS version 22. The chi-square test was used to compare proportions for categorical variables. Among the twelve recommendations, the proportions of women who stayed in healthcare facilities after delivery (100%) and who received postnatal examinations (97.3%) were satisfactory. However, intake of iron and folic acid during the postpartum period (86.4%), adoption of contraception (56.4%), and practice of postnatal exercises (15%) were considerably low. Maternal education and socioeconomic status were significantly associated with knowledge related to breastfeeding and postnatal iron and folic acid intake. Continuity of care from the antenatal to postnatal period is crucial yet limited. High-quality postnatal care should emphasize continuity, trust-building, consistent information, and recognition of women’s personal and cultural contexts.